Risk Management and Resilience: Summary of Learning on CGIAR’s Ways of Working - Humphrey, Sarah; Theuri, George (CGIAR Independent Advisory and Evaluation Service, 2025)
This summary of learning, prepared under the System Council–endorsed Multi-Year Evaluation Plan (MYEP), synthesizes evidence on CGIAR’s Ways of Working (WoWs) identified in the CGIAR 2030 Research and Innovation Strategy as priority approaches for CGIAR to do business differently, namely: • Targeting risk-management and resilience as critical qualities for Food Land and Water systems.